2018
DOI: 10.30574/gscbps.2018.5.2.0110
|View full text |Cite
|
Sign up to set email alerts
|

Antifeedant effect of Brassica nigra seeds against cotton leafworm Spodoptera littoralis and its potential antibacterial activity

Abstract: Water extract of mustard seeds (Brassica nigra L.) at 40, 20 and 10% concentrations were applied to evaluate the bioactivity of mustard seed extract against the 4th instar larvae of cotton leafworm Spodoptera littoralis. Increasing concentration of mustard extracts exhibited anti-feedant activity. Antibacterial potential of mustard seeds was determined using the disc diffusion test against 10 bacterial strains; Aqueous and acetone extracts showed very weak or no antibacterial activity ranging from 6.0 to 7.75 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
(7 reference statements)
0
2
0
Order By: Relevance
“…Callosobruchus chinensis L., 1758 (Coleoptera: Chrysomelidae) was found to be removed from the environment by the powder extracted from this plant (Li et al, 2008). Ali & Mohamed (2018) determined the effect of B. nigra seeds on Spodoptera littoralis Boisduval, 1833 (Lepidoptera: Noctuidae). It was reported that the seeds have the ability to prevent feeding on the harmful species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Callosobruchus chinensis L., 1758 (Coleoptera: Chrysomelidae) was found to be removed from the environment by the powder extracted from this plant (Li et al, 2008). Ali & Mohamed (2018) determined the effect of B. nigra seeds on Spodoptera littoralis Boisduval, 1833 (Lepidoptera: Noctuidae). It was reported that the seeds have the ability to prevent feeding on the harmful species.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, B. nigra EO, which is used against green peach aphid, was found to have some toxicity, especially at high concentrations, although less than other oils and it is suggested that it may be effective against this type of pest. Ali & Mohamed (2018) determined the effect of B. nigra seeds on Spodoptera littoralis Boisduval, 1833 (Lepidoptera: Noctuidae). It was reported that the seeds have the ability to prevent feeding on the harmful species.…”
Section: Discussionmentioning
confidence: 99%